Working Across Faultlines—Assessing Intersubgroup Communication in Teams - Straube, Julia; Kauffeld, Simone (Frontiers in Communication, 2021)
Communication between different subgroups is essential to group success, as different perspectives and knowledge need to be integrated. Especially when subgroups form due to faultlines, hypothetical dividing lines splitting a group into homogeneous subgroups, the resulting subgroups are vulnerable to negative intergroup processes. In this article, we evaluate different methods that have been used to trace communication between faultline-based subgroups and discuss challenges that researchers face when applying those methods. We further present the faultline communication index (FCI) as a novel approach to meet those challenges. We combine techniques from social network analysis with a behavioral process approach to trace communication processes between subgroups and provide scholars with tools to integrate in their own research. We illustrate this approach by observing and coding real time interactions in 29 organizational meetings. Results show that although functional faultline strength does not impact information exchange between subgroups, intersubgroup interactions positively relate to the quality of action plans defined at the end of a meeting. Managers and practitioners who work with diverse teams can be given guidance on how communication between subgroups evolves and how it can be shaped to become more effective. We further discuss implications for future research on communication between subgroups.